CONTRASTIVE STUDY OF PHRASEOLOGICAL UNITS WITH A FOOT COMPONENT IN ENGLISH AND UZBEK LANGUAGES (International Conference on Modern Science and Scientific Studies, 2025)
Phraseological units are an essential part of any language, reflecting national culture, traditions, and worldviews. The concept of "foot" is frequently used in phraseology to convey various meanings related to movement, stability, and social status. This article examines the similarities and differences between phraseological units containing the "foot" component in English and Uzbek languages, analyzing their semantics and cultural significance.